Melampus in Callimachus and Hesiod - Kampakoglou, A (Classical Association of the Middle West and South, 2017)
Fr. 54e Harder derives from Heracles' speech to Molorcus before he kills the Nemean Lion in Callimachus' Victoria Berenices. The mention of Melampus at lines 5–6 has been interpreted as a parallel to Heracles' exploit (Parsons) or a reference to an Argive location where Melampus cured the Proetids (Harder). This paper argues that the Hesiodic Catalogue of Women is a plausible intertext for Melampus' Argive affiliation, unifying these two interpretations. Mirroring the structure of the Hesiodic epic, fr. 54e presents a catalogue of Argive hero-kings who through their benefactions (Danaus, assuaging the drought; Melampus, curing the daughters of Proetus; Heracles, killing the lion) parallel Berenice herself. The catalogue reflects Ptolemaic ideology: Berenice's victory expresses her royal charisma, benefits the kingdom and guarantees its stability.